Analysis of a dilatation in a non-linearly elastic sphere - Zhang, Qingxian (2009)
A 2nd order non-linear elastic material has been successfully modeled as a 2-layered spherical shell bonded to a rigid core. Based on this model, the mechanical state described by 5 elastic parameters, λ, μ, l, m, and n is investigated. These parameters can be numerically manipulated to give desired properties for various functions. An application requiring minimal swelling of the bio-gel can be optimised by making the l and n values positive, while decreasing µ, l, m and n. On the other hand, an application requiring maximum swelling can be optimised by increasing λ and µ, while decreasing l and m.